Fire in Orbit: Equipping the Commercial Spaceflight Industry for Fighting Fire in Micro-Gravity - Cybela, Trent (Proceedings of the Wisconsin Space Conference, 2016)
For several years, Orbital Technologies (ORBITEC) has had keen interest in the development of a portable fire suppression system intended for use in commercial spaceflight applications. With the aid of recent developments in fine water mist (FWM) atomization technologies, and partnerships with the University of Wisconsin – Platteville, a portable fire extinguisher (PFE) prototype has been developed and constructed. The commercial extinguisher is capable of operation in both gravity and microgravity environments regardless of orientation, and eliminates the use of toxic carbon dioxide as a fluid suppressant. Preliminary testing of the PFE prototype has demonstrated promising discharge ranges and rates at various pressures. Testing has also confirmed the prototype’s ability to extinguish stored energy fires, in the form of lithium ion batteries.